The role of islet antigen presenting cells and the presentation of insulin in the initiation of autoimmune diabetes in the NOD mouse. Issue 1 (July 2016) - Unanue, Emil R.; Ferris, Stephen T.; Carrero, Javier A.
Summary: We have been examining antigen presentation and the antigen presenting cells (APCs) in the islets of Langerhans of the non‐obese diabetic (NOD) mouse. The purpose is to identify the earliest events that initiate autoimmunity in this confined tissue. Islets normally have a population of macrophages that is distinct from those that inhabit the exocrine pancreas. Also found in NOD islets is a minor population of dendritic cells (DCs) that bear the CD103 integrin. We find close interactions between beta cells and the two APCs that result in the initiation of the autoimmunity. Even under non‐inflammatory conditions, beta cells transfer insulin‐containing vesicles to the APCs of the islet. This reaction requires live cells and intimate contact. The autoimmune process starts in islets with the entrance of CD4 + T cells and an increase in the CD103 + DCs. Mice deficient in the Batf3 transcription factor never develop diabetes due to the absence of the CD103/CD8α lineage of DCs. We hypothesize that the 12–20 peptide of the beta chain of insulin is responsible for activation of the initial CD4 + T‐cell response during diabetogenesis.